KUALITAS KEBERSIHAN, FASILITAS, DESAIN DAN PENGELOLAAN TOILET UMUM PADA DAYA TARIK WISATA DI BALI (Jurnal Ilmiah Pariwisata, 2014)
The aim of this research was to identify the management system of public toilet in several tourist attractions in Bali, which was related to cleanliness quality, facility, and design feasibility. In addition, this was also referred to identifying the level of tourist’s satisfaction as user of public toilet. To achieve those goals, this research used survey design to collect data of 200 respondents in 20 tourist attractions spread in Bali. Focus Group Discussion (FGD) was conducted to reconfirm the findings; therefore right strategies could be formulated to overcome current issues and problems. The analysis method applied for this research was Qualitative Descriptive and Performance-Importance Analysis. The results showed that tourist’s satisfaction toward the cleanliness and design of public toilet was 47%. From design feasibility perspective, it was found out that conformance level of public toilet design toward international standard was 51%. Those findings showed that the public toilet management system in Bali needed significant improvement. It needed a comprehensive approach to solve these problems by involving all stakeholders.